If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 1 + 2x + 1 + x + x = 162 Reorder the terms: 1 + 1 + 2x + 2x + x + x = 162 Combine like terms: 1 + 1 = 2 2 + 2x + 2x + x + x = 162 Combine like terms: 2x + 2x = 4x 2 + 4x + x + x = 162 Combine like terms: 4x + x = 5x 2 + 5x + x = 162 Combine like terms: 5x + x = 6x 2 + 6x = 162 Solving 2 + 6x = 162 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6x = 162 + -2 Combine like terms: 2 + -2 = 0 0 + 6x = 162 + -2 6x = 162 + -2 Combine like terms: 162 + -2 = 160 6x = 160 Divide each side by '6'. x = 26.66666667 Simplifying x = 26.66666667
| 14x^2-9x+5=4 | | 3n+2.5=6.1 | | x(9x+16)=4x^2-20x+81 | | 0=-16x^2+48x+0 | | -x^2+3x-30=0 | | 0=-16x+48x+0 | | 7+(-7x+(-5))=3(4-2x)-9 | | 2k(k+5)=5 | | 5x-15=3x+19 | | x^2+120x-869=0 | | 9x+6x+2=0 | | 9x^2+16x-5=-1 | | x^4-3x^3-14x^2+12x+40=0 | | 2k(k+15)=15 | | 0+2y=-10 | | -16+200+25=0 | | x+2(0)=-10 | | 27+5x=-8 | | x+2(-3)=-10 | | 10x^2-6xy-4y^2= | | 6+2y=-10 | | 8x^3-14x^2-18x=0 | | -9x+3=-30 | | y=4(7)+6 | | 4(2x+6-2)=72 | | 4(2x+6)-2=72 | | 5x-7=7x+11 | | 4x^2+x-4=0 | | 4(2x)+6-2=72 | | 6x-3=13-2x | | -(-7x-9y-9)= | | 4(2x-4)= |